2012
DOI: 10.1089/thy.2011.0121
|View full text |Cite
|
Sign up to set email alerts
|

In Papillary Thyroid Cancer, Preoperative Central Neck Ultrasound Detects Only Macroscopic Surgical Disease, But Negative Findings Predict Excellent Long-Term Regional Control and Survival

Abstract: Background: Ultrasound (US) of the central neck compartment (CNC) is considered of limited sensitivity for nodal spread in papillary thyroid cancer (PTC); elective neck dissection is commonly advocated even in the absence of sonographic abnormalities. We hypothesized that US is an accurate predictor for long-term diseasefree survival, regardless of the use of elective central neck dissection in patients with PTC. Methods: A retrospective chart review of 331 consecutive PTC patients treated with total thyroidec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 33 publications
1
66
1
3
Order By: Relevance
“…However, there remains little evidence to suggest that microscopic disease, not visible on preoperative imaging or intraoperative palpation, is associated with poorer outcomes. Furthermore, there is little evidence to suggest that the resection of such microscopic disease in prophylactic central neck dissection improves overall survival [45,46]. Advocates for prophylactic central neck dissection argue that this procedure provides more accurate assessment of nodal status.…”
Section: • Controversy Over Management Of Nodal Diseasementioning
confidence: 99%
“…However, there remains little evidence to suggest that microscopic disease, not visible on preoperative imaging or intraoperative palpation, is associated with poorer outcomes. Furthermore, there is little evidence to suggest that the resection of such microscopic disease in prophylactic central neck dissection improves overall survival [45,46]. Advocates for prophylactic central neck dissection argue that this procedure provides more accurate assessment of nodal status.…”
Section: • Controversy Over Management Of Nodal Diseasementioning
confidence: 99%
“…The surgical management of the central neck in patients without documented metastatic disease remains controversial and some suggested that prophylactic central neck dissection leads to an increase in pN1 disease that seems not to affect prognosis (18,19,20). In this study, 184 (63%) patients underwent prophylactic central neck dissection and there was no increase in recurrences in cN1 disease compared with cN0 disease.…”
Section: Discussionmentioning
confidence: 69%
“…There was no case of death due to the disease. (9)(10)(11)(12)(13)(14), the presence of more than 5 positive LN (11,(15)(16)(17)(18), metastases ≥ 3 cm (11,16,19), and extranodal extension (15,16,(18)(19)(20)(21) are also associated with a poor prognosis (4,5,7,22). In these cases, there is little controversy about the need for a more aggressive initial approach.…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurmentioning
confidence: 99%
“…Furthermore, the risk of persistent disease [defined as metastases on initial posttherapy whole body scanning (RxWBS) or detected by the imaging methods until one year after ablation] and tumor recurrence (defined as strutural disease diagnosed more than one year after ablation) is significantly increased when LNM are detected by preoperative US (9)(10)(11)(12)(13)(14), in the presence of numerous [> 5 positive LN (11,(15)(16)(17)(18)] and large LNM [≥ 3 cm (11,16,19)], or in the presence of extranodal tumor extension (15,16,18-21).…”
Section: Introductionmentioning
confidence: 99%